Regression-based evaluation of the flexural response of reinforced concrete beams made with sustainable electrical insulator waste - R., Ranjith; S. K., Sekar (Frontiers in Built Environment, 2025)
The use of sustainable industrial waste composites in reinforced concrete structural applications will be eco-friendly. The aim of the present study is to evaluate the regression-based flexural response of reinforced concrete beams by using ceramic electrical insulator waste as a substitute for cement and aggregate. The assessment of flexural behavior is presented in this study from bending stress, deflection, and crack width measurements. It details an experimental program suitably designed and tested to evaluate the responses of reinforced insulator concrete beams (flexure, shear and bond types) and generate the regression modeling. The results indicate that, in comparison to the reference beams (M1 F, M1 B, and M1 S), the bending stress of flexure- (M4 F), bond- (M4 B), and shear-reinforced (M4 S) insulator concrete beams increased by 17.41%, 13.52%, and 27.77%, respectively. The deflection values of flexure- (M4 F), bond- (M4 B), and shear-reinforced (M4 S) insulator concrete beams decreased by 10%, 8%, and 17%, respectively, compared to the reference beams. Similarly, the crack width of flexure- (M4 F), bond- (M4 B), and shear-reinforced (M4 S) insulator concrete beams decreased by 35%, 34.72%, and 35.07%, respectively, compared to the reference beams. The difference between regression and experimentally predicted results showed less than 4% error. The regression- predicted that R2 values were more than 97%. The regression correlation reveals that there exists a close relationship among bending stress, deflection, and crack width in the first crack stage, service stage, yield stage, and ultimate stage. The sustainability factors obtained, such as energy consumption (Ec = 3521.78 MJ/m3), CO2 emission reduction (CO2e = 781.37 kg/m3), and cost benefit of 24.41%, were benefits of the study. Overall, the experimental findings aligned well with regression prediction and also demonstrate that insulator waste can be utilized to produce sustainable and cost-effective reinforced concrete without compromising structural performance.